Indoor exposure to particulate matter and the incidence of acute lower respiratory infections among children: A birth cohort study in urban Bangladesh. (21st March 2013) - Gurley, E. S.; Homaira, N.; Salje, H.; Ram, P. K.; Haque, R.; Petri, W.; Bresee, J.; Moss, W. J.; Breysse, P.; Luby, S. P.; Azziz‐Baumgartner, E.
Abstract: Approximately half of all children under two years of age in Bangladesh suffer from an acute lower respiratory infection (ALRI) each year. Exposure to indoor biomass smoke has been consistently associated with an increased risk of ALRI in young children. Our aim was to estimate the effect of indoor exposure to particulate matter (PM2.5 ) on the incidence of ALRI among children in a low‐income, urban community in Bangladesh. We followed 257 children through two years of age to determine their frequency of ALRI and measured the PM2.5 concentrations in their sleeping space. Poisson regression was used to estimate the association between ALRI and the number of hours per day that PM2.5 concentrations exceeded 100 μg/m 3, adjusting for known confounders. Each hour that PM2.5 concentrations exceeded 100 μg/m 3 was associated with a 7% increase in incidence of ALRI among children aged 0–11 months (adjusted incidence rate ratio (IRR) 1.07, 95% CI 1.01–1.14), but not in children 12–23 months old (adjusted IRR 1.00, 95% CI 0.92–1.09). Results from this study suggest that reducing indoor PM2.5 exposure could decrease the frequency of ALRI among infants, the children at highest risk of death from these infections.